Penerapan Sistem Bukti Lulus Uji Elektronik (BLU-e) dalam Pelayanan Pengujian Kendaraan Bermotor di Dinas Perhubungan Kabupaten Timor Tengah Utara - Bere, Delviana Magdalena; Fernandes, Dominikus; Mau, Alfred Omri Ena; Adam, Cataryn V. (Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to describe the implementation of the Electronic Test Pass Certificate (BLU-e) system in motor vehicle testing at the Transportation Agency of North Central Timor Regency. The main issue in this research is the lack of participation and awareness among motor vehicle owners regarding the importance of regular periodic testing. In this study, the research method used is field research with a descriptive qualitative approach. The theory used in this research is the implementation theory proposed by Edward III, which highlights communication, resources, disposition, and bureaucratic structure. The research results show that in the policy of replacing the logbook with the BLU-e system, communication is effective but the socialization related to the BLU-e system has not been thoroughly conducted, the available human resources are limited and there has been no increase in the number of employees, equipment resources are inadequate and often experience damage, but the Transportation Agency of TTU Regency shows very good disposition by providing a positive response as the implementer of the logbook replacement policy with the BLU-e system. The bureaucratic structure of the Transportation Agency of TTU Regency shows clear division of labor and functional boundaries, despite facing challenges such as limited staff and vacant positions. However, effective division of responsibilities and collaboration between teams successfully supported the implementation of the BLU-e system.